Shared projects and symbiotic collaborations: Shenzhen and London in comparative conversation. (June 2022) - Teo, Shaun SK
This paper presents 'shared projects' and the 'symbiotic' relations they engender to capture accounts of state and society actors collaborating to turn individual constraints into collective opportunities for pursuing urban experiments which are institutionally-shaped but also institution-shaping. The concepts are developed through a sequential and recursive comparison – that is, a 'comparative conversation'– between a case of urban village upgrading in Shenzhen and Community Land Trust Development in London. The paper uses a pragmatist approach to capitalist transformation as a starting point for comparison between these supposedly 'incomparable' cases. I build both heterogeneous and generalisable accounts of the pathways and progressive potential of collaborations on shared projects by recursively composing analytical proximities across the cases and their contexts of state entrepreneurialism and austerity localism. Theoretically, this paper contributes to scholarship which focuses on the contingency and complexity inherent in urban transformation. State and society actors are seen as potential collaborators working pragmatically to solve systemic problems without necessarily targeting wholesale systemic change. Methodologically, it contributes to ongoing attempts to demonstrate the positive relationship between experimental comparisons and conceptual innovation through staging a 'comparative conversation'.